Inhibition of Hippocampal Matrix Metalloproteinase-3 and -9 Disrupts Spatial Memory. (13th December 2006) - Wright, John W.; Brown, Travis E.; Harding, Joseph W.
Abstract : Memory consolidation requires synaptic reconfiguration dependent upon extracellular matrix (ECM) molecules interacting with cell adhesion molecules. Matrix metalloproteinase (MMP) activity is responsible for transient alterations in the ECM that may be prerequisite to hippocampal-dependent learning. In support of this hypothesis we have measured increases in MMP-3 and MMP-9 levels within the hippocampus and prefrontal cortex during Morris water maze training. The present investigation extends these findings by determining that infusion of an MMP inhibitor (FN-439) into the dorsal hippocampus disrupted acquisition of this task. In vitro fluorescence enzyme assays to determine the specificity of FN-439 against the catalytic domains of MMP-3 and MMP-9 indicated mean± SEMIC 50 s of 16.2± 7.8 and 210.5± 37.8μ M, respectively, while in situ zymography using hippocampal sections treated with FN-439 indicated significant reductions in MMP gelatinase activity. These results suggest that compromising the ability of the dorsal hippocampus to reconfigure ECM molecules by inhibiting MMP activity interferes with appropriate spatial memory acquisition, and support a role for hippocampal MMPs in the phenomena of spatial memory acquisition and storage.